Penggunaan Prinsip De Minimis Pada Ciptaan Program Komputer Berdasarkan Undang-Undang No. 28 Tahun 2014 Tentang Hak Cipta - Wardhana, Kesuma (Jurnal Hukum & Pembangunan, 2017)
Based on Indonesia’s current law, computer program is considered as a copyrightable works in accordance to Act No. 28/2014, which has accommodated computer program as a unique works that needs its own kind of protection. The act in question, unfortunately, is far from perfect, and has its own shortcomings, particularly because it doesn’t regulate nor state what elements it’s supposed to protect. This research therefor hopes to create boundaries and approaches that can be used both on a copyright infringement cases and to create a better legislation concerning the protection of computer program by the use of the de minimis principle